A novel para-amino salicylic acid magnesium layered hydroxide nanocomposite anti-tuberculosis drug delivery system with enhanced in vitro therapeutic and anti-inflammatory properties - Saifullah, Bullo; Arulselvan, Palanisamy; El Zowalaty, Mohamed E.; Woan, Sean Tan; Fakurazi, Sharida; Webster, Thomas J.; Baby, Rabia; Hussein, Mohd Zobir (Dove Press, 2021)
Introduction: Mycobacterium tuberculosis infections are associated with severe local inflammatory reactions, which may be life-threatening and lead to tuberculosis pathogenesis and associated complications. Inorganic nanolayers have been vastly exploited for biomedical applications (especially in drug delivery) because of their biocompatible and biodegradable nature with the ability to release a drug in a sustained manner. Herein, we report a new nanodelivery system of inorganic nanolayers based on magnesium layered hydroxides (MgLH) and a successfully intercalated anti-tuberculosis drug para-aminosalicylic acid (PAS). Methods: The designed anti-tuberculosis nanodelivery composite, MgLH-PAS, was prepared by a novel co-precipitation method using MgNO3 as well MgO as starting materials. Results: The designed nano-formulation, PAS-MgLH, showed good antimycobacterial and antimicrobial activities with significant synergistic anti-inflammatory effects on the suppression of lipopolysaccharide (LPS) stimulated inflammatory mediators in RAW 264.7 macrophages. The designed nano-formulation was also found to be biocompatible with human normal lung cells (MRC-5) and 3T3 fibroblast cells. Furthermore, the in vitro release of PAS from PAS-MgLH was found to be sustained in human body simulated phosphate buffer saline (PBS) solutions of pH 7.4 and pH 4.8. Discussion: The results of the present study are highly encouraging for further in vivo studies. This new nanodelivery system, MgLH, can be exploited in the delivery of other drugs and in numerous other biomedical applications as well.